Current Trends and Perspectives in Tyre Industry - Chicu, Nicoleta; Prioteasa, Adina-Liliana; Deaconu , Alecxandrina (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The digital age or the 4.0 industry makes its presence felt in all areas of the economy, making serious contributions to its development. The automotive industry is in a phase of change, acting on all its sub-industries such as the automotive tyre industry. We are witnessing a process in which large companies no longer sell a simple car or basic tyres, but resort to new technologies and digitalization to sell complex services tailored to the needs of consumers. Terms such as connectivity, mobility, autonomy became the main pillars in the development of such solutions integrated in the current market. Based on a SWOT analysis and a focus group organized with specialists from the field, this article aims to highlight the tyre industry market, which are the latest trends in the technologies used for development of the tyre industry, which are the factors that contribute to its growth and which are the threats, the opportunities for the big competitors in the market: Bridgestone, Goodyear, Michelin and Pirelli.